Meningkatkan Prestasi Belajar PAK Melalui Problem Based Learning (PBL) Materi Panggilan dan Perutusan Murid Yesus Kelas 8-1 SMP Negeri 1 Hiliserangkai Semester Ganjil - Noferlin Batee; Timotius Tote Jelahu; Modestus Haryono; Marta Lea Resti Prana Widya; Nikodimus M.K; Maria Junai (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve the learning achievement of participants in Catholic Religious Education and Character Education for class VIII-1 students at SMP Negeri 1 Hiliserangkai for the 2024/2025 academic year in the subjects of Catholic Religious Education and Character Education through the application of the Problem Based Learning (PBL) learning model. This type of research is Classroom Action Research (PTK) which is carried out in two cycles with 2 meetings per cycle. Each cycle consists of several stages, namely planning, implementing actions, observing and reflecting. The first and second cycles discuss the material on the Call and Mission of Jesus' Disciples and the Consequences of Jesus' Preaching. The subjects in this research were Catholic students in class VIII-1 of SMP Negeri 1 Hiliserangkai for the 2024/2025 academic year, consisting of 21 people. The main techniques for collecting data are carried out by means of tests and observations, while supporting techniques use interviews and documentation. The results of the research show that the application of the Problem Based Learning (PBL) learning model can improve the learning outcomes of class VIII-1 students starting from cycle I and cycle II, namely 81 in cycle I, increasing to 89 in cycle II. The conclusion of this research is that the application of the Problem Based Learning (PBL) learning model assisted by the interactive media of jingling buttons can improve the learning outcomes of Catholic Religious Education and Character for students in class VIII-1 of SMP Negeri 1 Hiliserangkai for the 2024/2025 academic year.